Periacetabular osteotomy of the hip: the ilioinguinal approach - Pogliacomi, F.; Stark, A.; Vaienti, et al., E. (Acta Biomedica Atenei Parmensis, 2003)
Developmental hip dysplasia (DDH) is characterized by an anomalous growth of the hip joint. Without adequate treatment, the natural history of DDH is development of secondary osteoarthritis in adulthood. The correction of the deformities modifies the biomechanics of the hip, which is important in order to slow down the progression of osteoarthritis and maybe to prevent and postpone this development. The Bernese periacetabular osteotomy is a procedure which reorientates the acetabular articular surface. Several surgical approaches have been used to achieve the same effective osteotomy. No surgical approach represents “the optimum”, with selection of appropriate exposure representing a balance of advantages and disadvantages. We used the ilioinguinal approach in 32 periacetabular osteotomies for acetabular dysplasia performed between 1996 and 2002. The operation was successful in 30 patients with acceptable operation time and blood loss and few complications. The advantages and disadvantages with the ilioinguinal approach as compared to other possibile incisions are discussed.